KERAGAMAN JAMUR DI KAWASAN HUTAN WANGKUNG KECAMATAN NDOSO KABUPATEN MANGGARAI BARAT - Humardani Syam Pratomo, Ryan; Mukminati Nur, Sri; Herlina (Jurnal Biogenerasi, 2023)
Mushroomdiversity in the Wangkung forest area, Ndoso district, West Manggarai Regency. This research is a survey research that aims to observe and find out the diversity of mushroom species in the Wangkung Forest Area, Ndoso discrict, West Manggarai Regency. The method used in this research is the quandrant transect method. The area or research location used is 500 meters long and 50 meters wide which is divided into 5 stations. The size of the transect is 2x2 meters, totaling 5 transect and will be randomly distributed at each stations. The results of this study showed that there were five types of fungi, namely: Auricularia polytricha as many as 104 species, Lentinus strigosus as many as 74 species, Trametes versicolor as many as 70 species, Pycnoporus sanguineus as many as 70 species and Lentinus sp as many as 37 species. Based on the results of the calculations of the diversity index of 1,533 which indicates the category of the diversity index is moderate . While the evenness index value is 0,952 which indicates the distributions category of the typeof community structure is stable or good. The average value of the wealth index is 3.869 which indicates the medium type of wealth. While at station 1 is dominate d by Auricularia polytricha and Pycnoporus sanguineus with a dominance index value of 0.070. At station 2 the dominance index value is 0.111 which is dominated by Auricularia polytricha which shows the most dominant fungus at stations 2. Meanwhile at station 3 is dominated by Auricularia polytricha with a dominance index value of 0.099. While at stations 4 is dominated by Auricularia polytricha with a dominance index value of 0.114 . Meanwhile, at station 5, Lentinus strigosus is dominated by a dominance index value of 0.081.